Concentration Dependence of the Infrared Photoluminescence of Pr3+ in Fluoroindate Glasses - Ribeiro, Sidney J. L.
Infrared photoluminescence properties are investigated for Pr3+ containing fluoroindate glasses with formula (mol% compositions) (99-x)[ 40InF(3)-20SrF(2)-20BaF(2)-20ZnF(2)]:xPrF(3) (x= 0.1, 0.2, 0.5, 1.0 and 2.0 mol%). Different mechanisms of population and quenching for Pr3+ D-1(2) and (1)G(4) levels are shown from photoluminescence (PL), photoluminescence excitation (PLE) and decay time values. Cross relaxation processes are put in evidence in different ways for the population of excited levels as a function of the Pr3+ concentration, depending on the excitation wavelength. Different dependences on Pr3+ concentrations are observed for D-1(2) and (1)G(4) levels.